WORK SATISFACTION INFLUENCE TOWARD EMPLOYEE PROSPERITY - Rini Indryawati; Widiyarsih Widiyarsih (Universitas Gunadarma, 2007)
Work satisfaction has an effect to employee wealthy at PT. Nagaraja Lestari in taking the policy and to motivate employee to enhancing the work performance in giving wages, salary, incentives, job promotion and employee healthy. This research is using qualitative approach and using observation and interview as tool research. Data collecting is in naration, description, story, written and unwritten documents. When employee has higher work satisfaction they will psychological wealthy fullfilness.Key words: work satisfaction, job performance